Hubungan Negara dan Agama dalam Pandangan Islam Kontemporer - Sudirman Sudirman (LP3M STITNU AL HIKMAH MOJOKERTO, 2020)
The relationship between state and religion can be seen based on the civilization that will relate to the community, both groups and cooperation that existed at that time. This relationship is an interesting discussion, because in the past the relationship between state and religion was one of the biggest problems, because the uneven distribution of religion made this inseparable from the understanding of various groups. The factor that makes this relationship complicated is the absence of the right leader who can be relied on to find a solution to the problem. This study aims to explain the relationship between state and religion in the perspective of contemporary Islam so that we can see the relationship between these two in the past. The research method used is descriptive research so that we can see a picture of the events that occurred during the lamp period. The results in this study indicate that the role of leaders in the relationship between state and religion is one of the factors supporting the spread of religion in the past.